Exploring the correlation between self-evaluation and exercise intentions among Rivers Youths in Nigeria - Hart, Fred Owonte (Faculty of Natural and Applied Sciences Journal of Health, Sports Science and Recreation, 2024)
This study explored the correlation between self-evaluation and exercise intentions among Rivers Youths in Nigeria. The study was carried out in Rivers State, one of the states in the southern part of Nigeria, situated in the Niger Delta region. The study design was a descriptive survey. The population comprised all youths in the three senatorial districts in the state. The sample size was 426 calculated using the Cochran formula with a non-compliance rate of 10%. A self-developed questionnaire was used for data collection with a retrieval rate of 95.5%. Data was analysed using mean and standard deviation to answer the research questions while the hypotheses were answered using PPMC at 0.05 alpha level of significance. Results showed that the mean age of respondents was 21.38±3.36 years. There were more females (63.6%) than males (36.4%) in the study, the majority had attained tertiary education (69.8%), were single (84.8%), unemployed (57.5%), in the middle class (62.2%) and were Christians (87.0%). Intention to exercise was above average. Respondents with low self-esteem (40.7%), poor self-image (53.4%) and were rarely influenced by peers (45.5%) indicated that they were unlikely to exercise. There was a significant correlation between self-esteem (r=0.357; p=0.000), self-image (r=0.558; p=0.000), peer influence (r=0.276; p=0.000) and intention to exercise among youths in Rivers State. it was recommended that parents and guardians should model active lifestyles and create opportunities for family-based activities; in addition, Non-governmental organizations focused on youths should design programmes where influential youths are encouraged to spread the message of fitness and wellbeing among their peers leveraging peer influence for positive outcomes.